2012
DOI: 10.3892/mmr.2012.899
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II promotes the proliferation of endothelial progenitor cells through p38 and p44/42 MAPK activation

Abstract: Abstract. Urotensin II (UII) is a vasoactive peptide with many potent effects in the cardiorenovascular system and is also possibly involved in the pathogenesis of atherosclerosis. Endothelial progenitor cells (EPCs) are involved in angiogenesis and vascular homeostasis and may be important in the maintenance of endothelial integrity. The aim of this study was to investigate whether UII has an effect on the proliferation of bone marrow-derived EPCs and the possible signaling mechanisms involved. Bone marrow-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The regulation of apoptosis in endothelial cells is critical for the integrity of endothelium. Studies also found that U-II promote the proliferation of rat bone marrow-derived EPCs through a process that involves ERK activation [29] . In our study, we examined the potential inhibited apoptosis function of U-II in HUVEC and the role of PI3K/Akt and ERK signaling in this process.…”
Section: Discussionmentioning
confidence: 98%
“…The regulation of apoptosis in endothelial cells is critical for the integrity of endothelium. Studies also found that U-II promote the proliferation of rat bone marrow-derived EPCs through a process that involves ERK activation [29] . In our study, we examined the potential inhibited apoptosis function of U-II in HUVEC and the role of PI3K/Akt and ERK signaling in this process.…”
Section: Discussionmentioning
confidence: 98%
“…Several signaling pathways have been implicated in the induction of IL-8 expression, including nuclear factor- κ B (NF- κ B)- and activating protein (AP)-1-dependent pathway which are activated by mitogen-activated protein kinases (MAPKs) pathway, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK) and p38 MAPK pathway in endothelial cells [10] , [11] . In addition, U-II has been shown to activate MAPK signal transduction pathways in different cell types [12] [14] . Although U-II has been found to induce the proliferation of endothelial cells [6] , its induction of IL-8 gene expression in vascular endothelial cells has not been studied, and the crosstalk between U-II and IL-8 in activation of endothelial cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…EPCs are pluripotent stem cells, which have the potential to differentiate into mature endothelial cells ( 37 ). However, the exact role of the SDF-1α/CXCR4 signaling pathway in EPC-mediated angiogenesis in osteosarcomas remains unclear.…”
Section: Discussionmentioning
confidence: 99%